1996
DOI: 10.3109/08880019609030803
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Episodes in Children with Cancer in the United Arab Emirates

Abstract: The febrile episodes encountered in our pediatric oncology unit over a 2-year period were reviewed. A total of 138 febrile episodes were recorded in 59 patients (29 with leukemia and 30 with a solid tumor). There was no difference in the number of episodes between leukemia and solid tumor patients, nor between neutropenic and non-neutropenic patients. The degree of neutropenia was more severe in leukemia patients. A total of 18.8% of the episodes were accompanied by positive blood cultures. Gram-positive bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
1
15
3
Order By: Relevance
“…Our data on the correlation of febrile episodes with microbiologically or clinically documented infections and their underlying pathogens were in keeping with the results of earlier studies [11,19,20,23,25,29,31]. Febrile episodes were associated with microbiologically or clinically documented infections in 60% of all cases, high-dose-cytarabine/asparaginase.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our data on the correlation of febrile episodes with microbiologically or clinically documented infections and their underlying pathogens were in keeping with the results of earlier studies [11,19,20,23,25,29,31]. Febrile episodes were associated with microbiologically or clinically documented infections in 60% of all cases, high-dose-cytarabine/asparaginase.…”
Section: Discussionsupporting
confidence: 86%
“…Fever was observed during approximately 24% of all chemotherapy cycles, with a mean total incidence of 2.8 febrile episodes per patient (2.5 febrile episodes per low-risk, 3.0 febrile episodes per high-risk patient). The total incidence of febrile episodes per patient in previous reports ranged from 2.6 to 4.2 [19,23,29]. Higher incidence rates can be partly explained by more aggressive chemotherapy regimens.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A total of 646 titles and abstracts were reviewed, of which 83 full‐text articles were retrieved. From this, 16 relevant articles, describing 15 studies, were identified for inclusion in this review (Figure ) . No dedicated NNF treatment guidelines were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the patient received antibiotics for 7-10 days. Average length of antibiotic therapy was 8.4 days in a study by Mahmood S et al 31 Rodriguez V et al 32 suggests in their study that it is important in patients apparently responding to antibiotics to continue treatment for a minimum of 7-10 days even if cultures prove sterile; too early cessation of treatment may cause relapse of infection and death.…”
Section: Discussionmentioning
confidence: 96%